An Approach to Extracting Sub-schema Similarities from Semantically Heterogeneous XML Schemas - De Meo, Pasquale; Quattrone, Giovanni; Terracina, Giorgio; Ursino, Domenico (Informatica)
An Approach to Extracting Sub-schema Similarities from Semantically Heterogeneous XML Schemas